Pengaruh Terapi Bekam Basah Terhadap Nyeri Kepala Pada Pasien Dengan Chepalgia Di Klinik Bekam Center Kota Bengkulu - A. Hafiz; Darmawansyah, Darmawansyah; Hermiati, Dilfera (Utami Publisher, 2025)
According to data from the World Health Organization (WHO) (2020), the prevalence of cephalgia in 2024 was 55%. In Indonesia, this figure is 722,084 people, while according to data from the Bengkulu City Health Office (2024), the incidence of cephalgia in Bengkulu City was 1,060. This study aimed to determine the effect of wet cupping therapy on headaches in cephalgia patients at the Bengkulu City Cupping Center Clinic. The research method used a quantitative approach with an uncontrolled pretest-posttest design. The sample consisted of 20 patients undergoing wet cupping therapy. Headache data were collected using a pain scale before and after therapy, then analyzed using the Wilcoxon test. The results showed a decrease in the average headache score from 5.00 to 3.25 with a significance value of p = 0.001, indicating a significant effect of wet cupping therapy on headache reduction. Wet cupping therapy is effective in reducing headaches in cephalgia patients at the Bengkulu City Cupping Center Clinic. It is suggested that wet cupping therapy can be used as an alternative non-pharmacological treatment for headache patients.